Neural precursor cell-expressed developmentally down-regulated 4-like: a new biomarker in the pathophysiology of endometrial cancer. Issue 9 (September 2018) - Yilmaz, Ercan; Gul, Mehmet; Melekoglu, Rauf; Inci Coskun, Ebru; Sahin, Nurhan; Gul, Semir; Bastemur, Ayse Gulcin; Ciplak, Baris
Objectives: Endometrial cancer is the most frequent tumor of the female genital tract. Ubiquitin is a small protein (8.5 kDa) found in all eukaryotic cells, binds to substrate proteins via a three-phase enzymatic pathway referred to as ubiquitination and plays an important role in cellular stability. Neural precursor cell-expressed developmentally down-regulated 4-like (NEDD4L) functions in the last phase of this enzymatic process. In this study, we investigated NEDD4L protein expression in endometrial cancer. Methods: The study participants were divided into patients with benign endometrial pathologies (Group 1, n = 23), patients with endometrial hyperplasia (Group 2, n = 21) and patients with endometrial cancer (Group 3, n = 20). NEDD4L expression was detected by immunohistochemical staining and H scores were calculated to standardize staining intensity. Statistical analysis was performed using SPSS 16.0. Results: NEDD4L expression levels according to H scores were significantly lower in patients diagnosed with endometrial cancer compared with those with benign endometrial pathologies. Conclusion: NEDD4L is involved in maintaining cell stability, and reduced NEDD4L expression as a result of gene mutation may disrupt this balance in favor of tumorigenesis.